Progression to invasive melanoma frommalignant melanoma in situ, lentigo maligna type - Tannous, Zeina (2000)
We have previously hypothesized that lesions that have been termed lentigo maligna can be divided into 2 categories: 1 represents a pigmented lesion that is a precursor to melanoma, and the other melanoma in situ. We and others have hypothesized that there is a progressive acquisition of attributes in pigmented lesions that results in malignant melanoma. Based on these 2 hypotheses, we have predicted that the intraepidermal component of invasive malignant melanomas, lentigo maligna type, should be similar to those lesions that we have termed malignant melanoma in situ, lentigo maligna type rather than lentigo maligna. The intraepidermal component of 42 consecutive cases of invasive malignant melanoma, lentigo maligna type was evaluated by all of the authors. Malignant melanoma in situ, lentigo maligna type is characterized by pagetoid spread, confluence, and nesting of atypical melanocytes. All of the cases evaluated showed features diagnostic of malignant melanoma in situ, lentigo maligna type, in the epidermis overlying the invasive dermal component. We conclude that invasive lentigo maligna melanoma arises in association with those lesions that we have termed malignant melanoma in situ, lentigo maligna type, which may represent a step in the progression between atypical melanocytic hyperplasia (lentigo maligna) and invasive melanoma. This fording supports the distinction of these entities and may have therapeutic implications.